FROM THE HISTORY OF THE MERITS OF GEORGIAN JEWS WHO SIGNED THE ACT OF INDEPENDENCE OF THE DEMOCRATIC REPUBLIC OF GEORGIA - Otar Nikoleishvili (World Scientific Reports, 2024)
In the history of the Democratic Republic of Georgia, alongside prominent Georgian public and political figures, significant contributions have been made by representatives of ethnically non-Georgian groups, including Georgian Jews. On May 26, 1918, the National Council of Georgia unanimously adopted the Act of Independence, which was signed by 88 members of the Council. Subsequently, on March 12, 1919, the newly elected Constituent Assembly re-approved the document with a minor amendment, which was endorsed by 13 additional signatories. Among these signatories were two Georgian Jews, Joseph Eligulashvili and Mose Davarashvili. Although only a few episodes of their social and political activities are discussed in this work, they serve to illustrate the significant role played by Georgian Jews in the state-building process of Georgia during this period